ENTOGPRENEURSHIP Dengan Memanfaatkan Limbah Rumah Potong Ayam (RPA) Sebagai Sumber Utama Pakan Ternak - Taufiqurrohman, Muhammad; Caroko, Sheptian Nur; Sugiarto, Muhammad Dwi (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
The increasing of chicken meat consumption will increase the number of Chicken Slaughter House(RPA). RPA is a special place to process the meat. However, However, it causes the increasing number of waste from unprocessed meat that may damage the environment. Whereas, the waste from RPA contains a huge amount of protein that can support entogâs (Cairinamoschata) growth and development. Entog is well known with its immunity against virus and bacteria. According to PKHDG(2011), demand for ducken meat, including entog, reaching 33,000 tons annually. Entog market price is also quite high. Lowest price per head reached Rp. 25.0600. Higher market entog males aged two months, around Rp. 50,000 per head. Entog was marketed in size from 2.6 to 3 kg for males, while females weighing 1.5 to 1.9kg. Utilization of waste as a source of live stock feed RPA is considered very advantageous, because the feed is readily available, abundant, cheap, highly nutria thousand not lead to residues in meat. The result is that we have sold 200 entogs (period I) and 110 entogs in period II with the total yield Rp.8.910.000 and the total profit Rp.2.400.000.Keywords : Entog, waste, Chicken Slaughtern House (RPA)